2022
DOI: 10.1097/hjh.0000000000003284
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model of hypertension resolution after adrenalectomy in primary aldosteronism: the SPAIN-ALDO score

Abstract: Purpose: To develop a predictive model of hypertension resolution after adrenalectomy in patients with primary aldosteronism (PA), based on their presurgical characteristics.Methods: A retrospective multicenter study of PA patients in follow-up in 20 Spanish tertiary hospitals between 2018 and 2021 was performed (SPAIN-ALDO Register). Clinical response postadrenalectomy was classified according to the primary aldosteronism surgical outcome (PASO) consensus criteria. The predictive model was developed using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…At the last follow-up, it was achieved in 31% of patients in the series of Vignaud ( 1 ). These results are in accordance with the reported in our Spanish registry, of 38% ( 14 ). Nevertheless, it should be noted that even biochemical cure without hypertension cure is associated with an improvement in the cardiometabolic risk and a major increase in health-related quality of life (HRQoL) after surgery.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…At the last follow-up, it was achieved in 31% of patients in the series of Vignaud ( 1 ). These results are in accordance with the reported in our Spanish registry, of 38% ( 14 ). Nevertheless, it should be noted that even biochemical cure without hypertension cure is associated with an improvement in the cardiometabolic risk and a major increase in health-related quality of life (HRQoL) after surgery.…”
supporting
confidence: 94%
“…In agreement with the results of the Eurocrine Study Group ( 1 ), the SPAIN-ALDO score includes female sex, use of two or fewer antihypertensive medications, hypertension grade 1, no type 2 diabetes and non-obesity as the predictive variables of hypertension cure. The chance of hypertension cure was 80.4% if all these variables were present before surgery ( 14 ). Nevertheless, in the Vignaud et al ( 1 ) study, body mass index, duration of hypertension, and number of antihypertensive drugs were the important predictive variables of hypertension cure identified on the multivariate analysis.…”
mentioning
confidence: 99%
“…38 Some researchers developed predictive models for postoperative hypertension cure in PA patients. 7,15,39,40 Female, shorter duration of hypertension, fewer number of antihypertensive drugs, and lower BMI are common predictors of hypertension cure. 7,15,39,40 Furthermore, external validation studies have shown the usefulness of these predictive models.…”
Section: Hyperkalemiamentioning
confidence: 99%
“…7,15,39,40 Female, shorter duration of hypertension, fewer number of antihypertensive drugs, and lower BMI are common predictors of hypertension cure. 7,15,39,40 Furthermore, external validation studies have shown the usefulness of these predictive models. 7,40 Counseling based on these models regarding probability of hypertension cure is recommended before surgery.…”
Section: Hyperkalemiamentioning
confidence: 99%
See 1 more Smart Citation